Marital status and living apart affect sleep quality in male military personnel: a study of the China’s Navy during COVID-19 - Guo, Xin; Meng, Yao; Lian, Hao; Li, Yinan; Xu, Ying; Zhang, Ruike; Xu, Jingzhou; Wang, Hao; Xu, Shuyu; Cai, Wenpeng; Xiao, Lei; Su, Tong; et al. (Frontiers in Psychiatry, 2023)
Background Marital status is a robust sociodemographic predictor of sleep. Having to live apart from spouse may have different implications than those of cohabitants or singles, especially in military personnel. Further research on this group will help provide knowledge in advance and facilitate early targeted interventions. Methods An online questionnaire study was conducted from July to November 2021. A total of 1,832 male military personnel completed the questionnaire. The marital status was measured by a self-reported single choice question. Pittsburgh sleep quality index (PSQI), Epworth Sleepiness Scale (ESS) and The Dysfunctional Beliefs and Attitudes about sleep scale (DBAS-16) were used to measure sleep-related outcomes. Inverse probability weighting (IPW) was applied to reduce the effects of confounding. Logistic regression was used to analyze the relationship between marital status and sleep and explore the impact of living together or not. Results After inverse probability weighting, the prevalence of poor sleep quality, sleepiness and dysfunctional beliefs were 16.1, 20.1 and 7.1%, respectively. One-way ANOVA results for the means of both groups were statistically significantly different, except for the sleep latency and sleep disturbance dimensions of PSQI. Participants who were married were more likely to have poor sleep quality (OR: 1.408, 95% CI: [1.10, 1.80]), to have daytime sleepiness (OR: 1.560, 95% CI: [1.27, 1.92]) and to develop dysfunctional beliefs and attitudes (OR: 2.497, 95% CI: [1.65, 3.80]) than those who were unmarried. Further analysis showed that the odds of developing poor sleep quality and DBAS in participants who married but living apart were significantly bigger than those unmarried (OR: 1.548 and 3.991, respectively.), while there were no significant differences in the odds of daytime sleepiness (OR: 0.738, p = 0.050). Age was a protective factor for the development of bad sleep outcomes, while family economic was an independent risk factor. Conclusion Marital status appear important for sleep quality, daytime sleepiness and sleep beliefs. The effect of living apart or not should be considered separately as an important predictor of sleep.